PENGARUH MODEL NUMBERED HEADS TOGETHER TERHADAP PEROLEHAN BELAJAR TEMATIK KELAS V SEKOLAH DASAR - Sumarni, Margaretha Lidya; Mashudi, Mashudi; Priyadi, Antonius Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research an experimental study that purpose to describe the influence of the numbered heads together model on the learning outcomes in fifth class of Elementary School in Rangkang, Bengkayang District, First Semester in 2019/2020. The study was conducted on 35 students in fifth class of Elementary School. The form of this research quasi-experimental research design with nonequivalent control group design. The average pretest score of students before implementing the learning model of numbered heads together was 69.59 and the average posttest of students was 85.61. To find out the effectiveness of the application of the numbered heads together model use Ngain score with the interpretation of effectiveness> 55 = effective, the average value of students by 56,1294. The results of hypothesis testing using analysis of variance at a level of 5% (0.05) obtained Fcount 7.797 means significant. From the calculation of effect size (ES), obtained 1.89 (large criteria). Then it can be concluded that there is a significant influence between the use of the role playing method on learning acquisition in fifth class of Elementary School in Rangkang.Keyword: Influence, Numbered heads together, Learning Outcomes